2020
DOI: 10.1155/2020/1721936
|View full text |Cite
|
Sign up to set email alerts
|

The History of Methicillin-Resistant Staphylococcus aureus in Brazil

Abstract: Since the emergence of MRSA in the 1960s, a gradual increase in infections by resistant bacteria has been observed. Clinical manifestations may vary from brand to critical condition due to host risk factors, as well as pathogen virulence and resistance. The high adaptability and pathogenic profile of MRSA clones contributed to its spread in hospital and community settings. In Brazil, the first MRSA isolates were reported in the late 1980s, and since then different genetic profiles, such as the Brazilian epidem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 239 publications
0
13
0
Order By: Relevance
“…Until the rise of CA-MRSA, the multidrug-resistant clone ST239-SCC mec IIIA, known as the Brazilian epidemic clone (BEC), and its variants predominated as nosocomial pathogens throughout the country. 15 , 16 , 17 In the early 2000s, the ST5-SCC mec IV clone, known as the pediatric clone, which was not multidrug-resistant at first, was identified in Brazilian hospitals. 18 , 19 Subsequently, this lineage seems to have developed multidrug resistance, as well as important virulence factors such as biofilm formation and enterotoxin production.…”
Section: Molecular Epidemiology Of Ca-mrsa In Brazilmentioning
confidence: 99%
See 1 more Smart Citation
“…Until the rise of CA-MRSA, the multidrug-resistant clone ST239-SCC mec IIIA, known as the Brazilian epidemic clone (BEC), and its variants predominated as nosocomial pathogens throughout the country. 15 , 16 , 17 In the early 2000s, the ST5-SCC mec IV clone, known as the pediatric clone, which was not multidrug-resistant at first, was identified in Brazilian hospitals. 18 , 19 Subsequently, this lineage seems to have developed multidrug resistance, as well as important virulence factors such as biofilm formation and enterotoxin production.…”
Section: Molecular Epidemiology Of Ca-mrsa In Brazilmentioning
confidence: 99%
“… 18 , 19 Subsequently, this lineage seems to have developed multidrug resistance, as well as important virulence factors such as biofilm formation and enterotoxin production. 15 , 20 …”
Section: Molecular Epidemiology Of Ca-mrsa In Brazilmentioning
confidence: 99%
“…Methicillin resistance, due to altered penicillin binding protein (PBP-2a), is encoded by the mecA gene present on a mobile genetic element present in staphylococcal cassette chromosome mec (SCC mec ) [ 11 ]. So far, 14 SCC mec sequence types have been reported [ 12 ]. Studies showed that CA-MRSA contain SCC mec types IV and V, mostly with the PVL gene, while HA-MRSA carry SCC mec types I, II and III [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glycopeptide antibiotics, such as vancomycin, are a last-resort treatment option for MRSA and enterococci infections [68,69]. In Brazil, several waves of resistance of S. aureus against antimicrobials have been reported, being the second and the fourth waves related to hospital- and community-acquired MRSA, respectively, with increasing numbers of resistant strains isolated in different hospitals in São Paulo [70,71]. Recent reports have suggested a concerning scenario, indicating that all Brazilian regions have notified the presence of MRSA strains, especially in the southeastern region, the most affected in the last decades [71].…”
Section: Discussionmentioning
confidence: 99%